Eddy current separation for recovery of non-ferrous metallic particles: A comprehensive review - Smith, York R.; Nagel, James R.; Rajamani, Raj K. (Minerals engineering, 2019)
•The idea of using eddy currents to recover nonferrous metallic particles dates back to 1889.•Modern-day eddy current separators are efficient at recovering nonferrous metallic particles.•A theoretical background for analytical models is reviewed and discussed.•Limitations of current designs and new designs and applications are presented. Eddy current separation (ECS) is a process used throughout the scrap recycling industry for sorting nonferrous metals from other nonmetallic fluff. The mechanism is based on the principle that a time-varying magnetic field will induce electrical current to flow throughout the body of a conductive particle. This current then reacts to the applied magnetic field by exhibiting a pronounced force of deflection, thereby separating the materials. The process is remarkably efficient and environmentally friendly, making it essential to the growth and sustainability of the metal recycling industry. In this review, we aim to summarize the available literature on eddy current separators for recovery of nonferrous metals. Although several different designs of eddy current separators have been examined through the years, the most common in use today remains the belt-driven rotary drum design. Limitations of the belt-driven rotary drum design are discussed as well as potential new designs and new applications for eddy current separators.